2017
DOI: 10.1080/00015385.2017.1410350
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented QRS complexes are associated with left ventricular dysfunction in patients with type-2 diabetes mellitus: a two-dimensional speckle tracking echocardiography study

Abstract: The current study included 178 consecutive patients diagnosed with type-2 DM. The patients included were separated into two groups: those with (n = 50) and without (n = 128) fQRS. The two groups were compared by obtaining LV strain values with STE. Statistically significant differences were also identified between fQRS(-) and fQRS (+) groups with respect to Lv-GLS (p < .001), maxLAVI (p = .020), minLAVI (p < .001), E velocity (p < .001), Em velocity (0.002), E/Em ratio (<0.001) SRe (p < .001), SRe/SRa ratio (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
4
14
0
Order By: Relevance
“…This suggests that 4DSTE may be useful for demonstrating early myocardial dysfunction in SS patients. It has been shown that the duration of exposure to factors causing myocardial involvement is related to the severity of myocardial dysfunction 26 . In this study, SS duration was strongly associated with GAS and GLS.…”
Section: Discussionsupporting
confidence: 48%
“…This suggests that 4DSTE may be useful for demonstrating early myocardial dysfunction in SS patients. It has been shown that the duration of exposure to factors causing myocardial involvement is related to the severity of myocardial dysfunction 26 . In this study, SS duration was strongly associated with GAS and GLS.…”
Section: Discussionsupporting
confidence: 48%
“…In contrast, the prevalence of fQRS in other population is significantly greater than healthy population. The prevalence of fQRS in patients with chronic kidney disease with preserved LVEF, metabolic syndrome, heart failure patients requiring resynchronization therapy, and diabetes mellitus was 60%, 26%, 41.5%, and 28%, respectively. In a former population‐based study, the fQRS in healthy middle‐aged individuals was frequent, but it did not affect the occurrence of cardiac death, arrhythmic death, and death from any causes during a mean of 30 years follow‐up .…”
Section: Discussionmentioning
confidence: 99%
“…The standard 12‐lead ECG can be suggestive of abnormal findings during echocardiographic findings and patients should be regularly followed up . In addition to the prognostic value of fQRS in patients with cardiovascular diseases, it has also been found to be associated with subclinical myocardial dysfunction in patients with coronary artery disease, diabetes mellitus, and chronic kidney disease . The assessment of myocardial tissue by conventional echocardiography is load‐ and angle‐dependent, but 2‐dimensional speckle‐tracking echocardiography (2D‐STE) lacks such a limitation for the evaluation of myocardial mechanics .…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, signi cant elevation in the frequency of fQRS has been observed in DM, MetS, and other diseases without obvious cardiovascular symptoms. Bayramoglu et al reported a prevalence of fQRS of 28% [23], Eren et al reported 37.5% [24] among DM in a Turkish population and using coronary angiography, Mahfouz reported 62% in Egyptian DM [25]. In previous studies on MetS, 20% of patients showed fQRS in one study [26], and 26.1% of MetS patients compared to 14.6% of control subjects in another [27].…”
Section: Discussionmentioning
confidence: 92%